Given the expression:
![12sin^2(x)-3=0](https://img.qammunity.org/2023/formulas/mathematics/college/75gr14hogiirfntkafzq7ozfn6x1v0wzsf.png)
To solve the expression, follow the steps below:
Step 01: Add 3 to both sides.
![\begin{gathered} 12sin^2(x)-3+3=0+3 \\ 12sin^2(x)=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/927xqnjzvrqnl0hd9eoh3bdzieq0y0dqbw.png)
Step 02: Divide both sides by 12.
![\begin{gathered} (12sin^2(x))/(12)=(3)/(12) \\ sin^2(x)=(1)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zqyctiz61wjl0kconys8ijahjxeayjhluh.png)
Step 03: Take the square root of both sides.
![\begin{gathered} √(sin^2(x))=\pm\sqrt{(1)/(4)} \\ sin(x)=\pm(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jpfr9zs02iw78vq2gibtf2uta8j27v3o71.png)
Step 04: Evaluate the results.
First, let's evaluate sin(x) = 1/2.
Sin(x) is positive in the first and in the second quadrant. Then,
![\begin{gathered} sin^(-1)((1)/(2))=x \\ x=(\pi)/(6),x=(5)/(6)\pi \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7h4e3gaury9sf8lwox61ief1c6a6v8twir.png)
Second, let's evaluate sin(x) = -1/2.
Sin(x) is negative in the third and in fourth quadrant. Then,
![\begin{gathered} sin^(-1)(-(1)/(2))=x \\ x=(7)/(6)\pi,x=(11)/(6)\pi \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1l9998dfat6b3f1apew6egpg8dbfoagqjt.png)
Answer:
![x=(\pi)/(6),x=(5)/(6)\pi,x=(7)/(6)\pi,x=(11)/(6)\pi](https://img.qammunity.org/2023/formulas/mathematics/college/18m2etty6rzejfa9ofk76av1g79frw3gm2.png)